2004
DOI: 10.1073/pnas.0400782101
|View full text |Cite
|
Sign up to set email alerts
|

A gene atlas of the mouse and human protein-encoding transcriptomes

Abstract: The tissue-specific pattern of mRNA expression can indicate important clues about gene function. High-density oligonucleotide arrays offer the opportunity to examine patterns of gene expression on a genome scale. Toward this end, we have designed custom arrays that interrogate the expression of the vast majority of protein-encoding human and mouse genes and have used them to profile a panel of 79 human and 61 mouse tissues. The resulting data set provides the expression patterns for thousands of predicted gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

113
3,415
4
11

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 3,156 publications
(3,543 citation statements)
references
References 37 publications
113
3,415
4
11
Order By: Relevance
“…To identify previously uncharacterized cell-surface-associated proteins, we applied a ranking strategy to all 555 orthologues and prioritized proteins with no previous links to cardiac function on the basis of phenotype ontology (http://www.informatics.jax. org) and cardiac enrichment on the basis of threefold upregulation in cardiac tissue, using publicly available microarrays 13 . This approach identified Tmem65 as our top candidate (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To identify previously uncharacterized cell-surface-associated proteins, we applied a ranking strategy to all 555 orthologues and prioritized proteins with no previous links to cardiac function on the basis of phenotype ontology (http://www.informatics.jax. org) and cardiac enrichment on the basis of threefold upregulation in cardiac tissue, using publicly available microarrays 13 . This approach identified Tmem65 as our top candidate (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among different human tissues, the maximum gene expression was found in the liver and peripheral blood leukocytes [6,22]. A large-scale analysis of the human transcriptome indicated that the PBEF gene is highly expressed in whole blood, over 100 times of the median abundance, while the expression in adipocytes is just about 2 times of the median abundance (GEO series GSE1133) [23].…”
Section: Discussionmentioning
confidence: 99%
“…Other HSPG genes, including syndecan-2, -3 and -4 and the six glypican genes, were not expressed ('absent' call) by most myeloma cell samples, and displayed a very weak signal compared to syndecan-1. This lack of expression cannot be attributed to a failed detection by a non-functional Affymetrix probeset, as a high expression of the 10 HSPG genes could be detected on various normal tissues according to the data available (Su et al, 2004) (data not shown). A further HSPG, the variant v3 of CD44, was very weakly expressed on HMCLs (MFI ranging from 5-15, data not shown), in agreement with previous reports (Derksen et al, 2002;Van Driel et al, 2002).…”
Section: Only Hs-binding Egf-family Members Have a Myeloma Cell Growtmentioning
confidence: 98%